"Don't Deport Our Daddies": Gendering State Deportation Practices and Immigrant Organizing. (February 2014) - Das Gupta, Monisha
New York based Families For Freedom (FFF) is among a handful of organizations that directly organize deportees and their families. Analyzing the organization's resignification of criminalized men of color as caregivers, I argue that current deportation policies and practices reorganize care work and kinship while tying gender and sexuality to national belonging. These policies and practices severely compromise the ability of migrant communities to socially reproduce themselves. Furthermore, the convergence of criminalization and immigration enforcement renders the kinship ties of deportable men illegible, and justifies their separation from their loved ones. Since FFF publicly supports men with criminal convictions, it reveals that its members become targets of deportation precisely because they do not and cannot conform to heteronormative prescriptions.